Analisis Pemahaman Konsep Siswa pada Materi Stoikiometri Menggunakan Tes Diagnostik Lima Tingkat di SMA Negeri 4 Gorontalo - Miftahul Nur; Nurhayati Bialangi; Julhim S. Tangio; Erni Mohamad; Erga Kurniawati; Astin Lukum (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
The principles of chemistry learning emphasize that students study chemical concept in a structure and detailed manner. Until now, chemistry lessons are still a big challenge for teachers, because students often experience difficulties when learning chemical concept such as the concept of stoichiometry. This study aims to determine the level of concept understanding and the percentage of students' concept understanding on stoichiometry material using a five tier diagnostic test. The method used in this research is descriptive qualitative. The results showed: (1) the average level of students' concept understanding is classified in the category of lack of knowledge (LK); (2) the average percentage of students who understand the concept (SC) is 13.0% and the sub-concept with the highest percentage of understanding the concept (SC) is Relative Molecular Mass which is 33.0%. Of the 15 questions tested, question number 1 has the highest percentage of understanding the concept (SC) of 33.0%, while for the other 14 questions the average student is classified in the category of lack of knowledge (LK). It can be concluded that students' concept understanding on stoichiometry material is still classified as very low criteria.